SAT0338 Prediction of cardiovascular events in patients with psoriatic arthritis: performance of five risk algorithms in an italian bicentric study. (12th June 2018) - Navarini, L.; Margiotta, D.P.E.; Caso, F.; Currado, D.; Tasso, M.; Angeletti, S.; Ciccozzi, M.; Scarpa, R.; Afeltra, A.; Costa, L.
Abstract : Background: The burden of cardiovascular (CV) risk in patients with psoriatic arthritis (PsA) is increased. Prediction of CV risk and consequent preventive strategies play a pivotal role in management of PsA. Recently, EULAR recommendations suggested to use a multiplication by the factor of 1.5 of original CV risk algorithms in patients with rheumatoid arthritis and other inflammatory arthritis. 1 Objectives: To evaluate the performance and calibration of five original and adapted according to EULAR recommendations CV risk algorithms in PsA: SCORE, CUORE, Framingham Risk Score (FRS), QRISK2, and Reynold's Risk Score (RRS). Methods: Prospectively collected data from two Central-Southern Italian cohorts of patients with an history of PsA of almost 10 years at November 2017 and without a personal history of CV disease (CVD) at baseline has been used. The primary outcome was the first CV event: sudden cardiac death, coronary artery diseases (CAD) (stable and unstable angina pectoris, myocardial infarction), cerebral vascular accident (CVA), transient ischaemic attack (TIA), peripheral artery disease (PAD) and heart failure (HF). Discriminatory ability for CV risk prediction was evaluated by the area under the receiver operating curve (ROC). Calibration between predicted risk and observed events was assessed by Hosmer-Lemeshow (HL) tests and calibration plots. Fisher's exact test has been used for analysis of contingency table 1, while Mann-Whitney test has been used to compare ranks. Sensibility, specificity, and odds ratio were calculated for low-to-intermediate risk cut-off (1% for SCORE, 10% for all the other algorithms) and for intermediate-to-high risk cut-off (5% for SCORE, 20% for all the other algorithms). Results: 155 patients (57±10.57 years) were enrolled with an observation of 1550 patient/year. During follow-up, 21 patients had a CV event (1.35 events per 100 patient/years): 8 cases of myocardial infarction or unstable angina pectoris, 3 cases of stable angina pectoris, 2 cases of TIA, 4 cases of PAD, 4 cases of HF. No fatal events were reported. Area under the ROC were 0.7679 (95% CI 0.64768 to 0.88812), 0.864 (95% CI 0.79675 to 0.93278), 0.7575 (95% CI 0.65784 to 0.85708), 0.8660 (95% CI 0.79428 to 0.93772), and 0.7183 (95% CI 0.57795 to 0.85862) for SCORE, CUORE, FRS, QRSIK2, and RRS, respectively, suggesting fair to good discriminative ability between patients with or without a CV event (figure 1). HL tests demonstrated poor model fit (p<0.05) for SCORE, CUORE, and RRS, but not for FRS and QRISK2 (p>0.05). Discriminative ability and calibration were not improved by adaption of the algorithms according to EULAR indications. A large amount of patients who experienced a CV event was at "low risk" (minimum 17.6% for SCORE and maximum 81.8% for RRS) or at "low-intermediate" risk (minimum 52.9% for SCORE and maximum 95.2% for FRS). Conclusions: Adaption of the CV risk algorithms according to EULAR indications did not provide improvement in discriminative ability and calibration in patients with PsA from Centre and South of Italy. In PsA, an excess of CV events has been observed in patients at "low risk" or "low-intermediate risk". Reference: [1] Agca R. et al. Ann Rheum Dis2017;76:17–28. Disclosure of Interest: None declared